Evaluation of innovative development of Ukrainian economy and determination of the mechanisms of its support - Zavadska, Diana (Technology audit and production reserves, 2017)
The aim of the article is to elaborate the recommendations as to the support of economic development and formation of Ukrainian infrastructural environment, favorable for innovations. In the result of research the evaluation of Ukrainian economic development was done. The objective necessity of industrial policy under conditions global competition was grounded. The tendencies of the changes of economies of the world leading countries were studied. The directions of realization of new industrial policy of Ukraine under conditions of the formation of new economy were determined. The institutional infrastructure of regional development as to attraction of foreign investments and transfer of new technologies in Ukrainian industrial sector was offered. It was proved, that the determinative role for overcoming of structural disproportions in Ukrainian economy is played by innovative processes, which favorable development is possible due to the long-term investment resources. Realization of the mechanisms of state-private partnership, stimulation of innovative policy by the instruments of state policy will provide multiplier effect from the economic technological base modernization. The accent was made on the fact that economic development institutions are the important instrument of state policy as to creation of favorable conditions for innovative infrastructure formation. It was noted, that the role of information center, combination of the functions of economic development institutes is given to the Agency of regional development, created on the principles of partnership between state, private and public sectors, directed on stimulation of socio-economic development.